Solid waste recycling in selected secondary schools - Durie, Ak Austine Tinggie (Universiti Malaysia Sarawak, (UNIMAS), 2007)
This study was carried out to gain information about the level of awareness, knowledge, attitude and opinion of the students and teachers toward recycling of solid waste, to investigate the current recycling practices at selected schools, to determine the volume of recycled waste collected by the schools, to find out what category of recycle waste produced, which waste is generated the most and to propose for future course of action in the efforts to improve their recycling capacity) 5 schools were selected for the study site i. e SMK Green Road, SMB St. Thomas, SMK Petra Jaya, SMK Tunku Abdul Rahman and SMK Tun Abang Haji Openg. The study approach and methodology were divided into social and field surveys. Questionnaires were distributed to 390 students and 60 teachers in the 5 schools, while the weight of the recyclable waste collected were recorded for a period of 8 weeks. The results form the interview showed that majority of the students and teachers have the awareness and knowledge on recycling of waste. The general attitude of students and teachers toward recycling, either practice or understanding were moderate. However overall, opinion about recycling practice was very positive. Majority of the student and teachers have the opinion that using school curriculum activities, participation acknowledgement and increasing the recycling facilities as ways to increase recycling participation. Majority of the students and teachers were undecided about the reason for not participating in recycling. All the 5 schools have established "Kelab Alain Sekitar" to manage the recycling programmes. Recycle waste collected from the schools and brought from home were sold to vendor. Money from the purchased were either given back to collector or used to support the recycling programmes. The volume of recycle waste collected from the 5 school for the period of 8 weeks were 3,330.5 kg (3.3 tonne). From the 5 categories (paper, plastic, metal, glass and other recycle wastes) paper constitute the higest recycle waste collected, the second higest is plastic bottle drink then followed by aluminium can drink.